Organizer restriction through modulation of Bozozok stability by the E3 ubiquitin ligase Lnx-like - Ro, Hyunju (2009)
The organizer anchors the primary embryonic axis, and balance between dorsal (organizer) and ventral domains is fundamental to body patterning. Ligand of Numb protein-X (LNX) is a RING finger and four PDZ domain containing E3 ubiquitin ligase1,2. LNX serves as a binding platform and may have a role in cell fate determination, but its in vivo functions are unknown1–5. Here we show that Lnx-l (Lnx-like) acts as a critical regulator of dorso-ventral (D-V) axis formation in zebrafish. Depletion of Lnx-l using specific antisense morpholinos (MO), caused strong embryonic dorsalization. We identified Bozozok (Boz; also called Dharma or Nieuwkoid) as a binding partner and substrate of Lnx-l. Boz is a homeodomain-containing transcriptional repressor induced by canonical Wnt signaling that is critical for dorsal organizer formation6–12. Lnx-l induced K48-linked polyubiquitination of Boz, leading to its proteasomal degradation in human 293T cells and in zebrafish embryos. Dorsalization induced by Boz overexpression was suppressed by raising the level of Lnx-l, but Lnx-l failed to counteract dorsalization caused by mutant Boz lacking a critical motif for Lnx-l binding. Further, dorsalization induced by depletion of Lnx-l was alleviated by attenuation of Boz expression. We conclude that Lnx-l modulates Boz activity to prevent the invasion of ventral regions of the embryo by organizer tissue. These studies introduce a ubiquitin ligase, Lnx-l, as a balancing modulator of axial patterning in the zebrafish embryo.